IDEOLOGICAL IMMUNITY AND ITS NEEDS (Scientific journal of the Fergana State University, 2023)
The article tried to reveal the concept of ideological ummunity, which is one of the main categories of the 21st century, its origin, original content and its importance in today's globalization conditions. In order to prove how important the need for ideological immunity is today, an attempt has been made to reveal information manipulation processes, its tools and methods, and the level of danger using examples. It is aimed to scientifically and analytically reveal the importance of ideological immunity in increasing the ideological knowledge, spiritual image and creative potential of our citizens, especially our youth, on the way to the development of our country.